SENSITIVE SKIN: A NEW ENTITY PERSPECTIVE - Putu Martha Gerynda Sukma; Windy Keumala Budianti; Sari Chairunnisa; Rinadewi Astriningrum (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Abstract: The phenomenon of “sensitive skin” is a relatively recent terminology in certain populations reporting sensory complaints that are more intense and more frequent than the normal population, especially after using cosmetic products. The incidence of sensitive skin is increasing along with the rapid widespread of skin care products availability. Various studies have been conducted but the pathophysiology of sensitive skin is still unclear. Physiological changes in sensitive skin are influenced by two main factors such as dysfunction in skin barrier and neurosensory. There are various quantitative sensory tests that can be done to determine skin sensitivity. Until now, there is no guideline for treating sensitive skin. Contributing factors, quantitative sensory tests, relation to skin diseases, and managements will be discussed in this literature review.Keywords: Dysfunction; Neurosensory; Sensitive skin; Skin barrier